Second-line failure and first experience with third-line antiretroviral therapy in Mumbai, India - Samsuddin Khan; Mrinalini Das; Aristomo Andries; Alaka Deshpande; Homa Mansoor; Peter Saranchuk; Petros Isaakidis (Taylor & Francis Group, 2014)
Background: There are limited data on the failure of second-line antiretroviral therapy (ART) and the use of third-line ART in people living with HIV in resource-limited settings. Since 2011, the Médecins Sans Frontières (MSF) HIV/tuberculosis programme in Mumbai, India, has been providing third-line ART to patients in care. Objective: To describe the experiences and programmatic challenges during management of suspected second-line ART failure and third-line ART therapy for patients living with HIV, including the use of HIV viral load (VL) testing. Design: This was a retrospective, observational cohort study of patients with suspected second-line ART treatment failure, who were followed for at least 12 months between January 2011 and March 2014. Results: A total of 47 patients with suspected second-line failure met the inclusion criteria during the study period. Twenty-nine of them (62%) responded to enhanced adherence support, had a subsequent undetectable VL after a median duration of 3 months and remained on second-line ART. The other 18 patients had to be initiated on a third-line ART regimen, which consisted of darunavir-ritonavir, raltegravir, and one or more appropriate nucleoside or nucleotide reverse transcriptase inhibitors, based on the results of HIV genotype testing. Of the 13 patients for whom follow-up VL results were available, 11 achieved virological suppression after a median duration of 3 months on third-line ART (interquartile range: 2.5-3.0). No serious treatment-related adverse events were recorded. Conclusions: With intensive counselling and adherence support in those suspected of failing second-line ART, unnecessary switching to more expensive third-line ART can be averted in the majority of cases. However, there is an increasing need for access to third-line ART medications such as darunavir and raltegravir, for which national ART programmes should be prepared. The cost of such medications and inadequate access to VL monitoring and HIV genotype testing are currently major barriers to optimal management of patients failing second-line ART.